Drinking Water and Liquid Waste Treatment - Siswanto, Siswanto; Nurfajriani, Nurfajriani (Indonesian Journal of Advanced Research, 2025)
This study seeks to explain the treatment processes of drinking water and wastewater, along with water source conservation practices in schools to sustain clean water availability. The approach combines literature review, policy analysis, and case studies of applied water treatment technologies. Findings indicate that drinking water treatment includes coagulation–flocculation, sedimentation, filtration, and disinfection, while wastewater undergoes primary, secondary, and tertiary stages. Case studies highlight the effectiveness of electrocoagulation, filtration, and plasma methods in reducing pollutants. In school settings, conservation is implemented through efficient water use, environmental greening, and plastic waste management. Overall, integrating treatment technologies with conservation initiatives contributes to improved health, quality of life, and environmental sustainability.